SIMULATION MEASUREMENT OF LOGISTIC MANAGEMENT PERFORMANCE USING BALANCE SCORECARD APPROACH WITH AHP ASSISTANCE TOOL (Study on Sanyere Craft Subang UKM) - Selda Sendara; Kuncorosidi Kuncorosidi; Estu Widarwati (JABI (Journal of Accounting and Business Issues), 2019)
This study is a simulation which aims to knowing the performance of logistic management to supports supply chain management activities in Sanyere Craft Subang SMEs. To measure the performance of logistics management the researcher proposes several Key Performance Indicators (KPIs) using Balance Scorecard approach related to logistics management. A total of 20 KPIs are proposed to SMEs owners and processed using AHP (Analityc Hierarchy Process). To knowing the level of logistic management performance then used descriptive survey method by providing questionnaires to respondents based of the Balanced Scorecard perspective. The results showing that from 20 KPIs obtained 4 KPIs priority that is Employee Skill, Cost of Ordering Material, Product Quality Assurance, and Production Scheduling. Overall the results of the analysis of the questionnaire data on the level of logistics management performance based on the 4 perspectives of Balance Scorecard are in the "good" category, which means that the logistical management activities in Sanyere Craft SMEs have gone well.